Meridian Energy and Project Aqua: a study in stakeholder identification and salience - Wells, Philippa Katherine (AUT Faculty of Business, 2006)
In 2004 Meridian Energy, a New Zealand State Owned Enterprise, announced its decision to cancel Project Aqua, a power generation scheme that would have involved the construction of six dams on the lower Waitaki river, in the South Island of New Zealand. The decision is interesting in terms of its implications for stakeholders who, as a consequence of transformation in the public sector, have arguably few formal avenues to pursue in challenging the decisions of managers of these enterprises. This paper applies a stakeholder identification/salience framework in exploring the position of, and strategies utilised by, those seeking identification and response from managers. A focus to this exploration is provided though reference to an important theme, that of the symbolic importance of the river – as location and as resource. The conclusion reached as a result of this exploration is that both those seeking recognition as stakeholders and decision-makers within organizations should be cognizant of the implications of socio-legal context on strategy and policy.